Global disruption: unveiling the educational metamorphosis triggered by COVID-19 - Basit, Abdul; Mohamad Zain, Jasni; Mojahid, Hafiza Zoya; Jumaat, Abdul Kadir; Hamdan, Nur’Izzati (Penerbit UiTM (UiTM Press), 2025)
The COVID-19 pandemic disrupted educational systems across more than 155 nations, affecting billions of students. This unprecedented crisis has accelerated the adoption of online learning, challenging traditional teaching methods and reshaping education in a matter of days. The transition to digital platforms revealed enhanced content retention and quicker learning curves among students in online environments. This study examines the integration of adaptive learning technologies with traditional methods, demonstrating their potential to create personalised and effective educational experiences. A key concern is whether these changes will persist beyond the pandemic. To address this, the study explores the long-term viability of digital adaptations and their potential to transform educational paradigms. This research provides insights into the pandemic’s impact on education and offers a roadmap for future practices. It highlights state-of-the-art technological applications that could redefine learning, ensuring education systems are better equipped to prepare for future disruptions.